Advanced Methods and Technologies for Agent and Multi-Agent Systems - Dariusz Barbucha, Robert J. Howlett, Lakhmi C. Jain (IOS Press, 2014)
The field of agent and multi-agent systems is concerned with the development and evaluation of sophisticated, AI-based, problem solving and control architectures for both single and multi-agent systems.